The Evolution of Titan's Cold South Polar Cloud - Lavender Elle Hanson; Robert S. French; Darryn W. Waugh; Erika L. Barth; Carrie M. Anderson (Geophysical Research Letters)
Abstract Early during Titan's southern fall, images captured by Cassini's Imaging Science Subsystem revealed the formation of a large cloud above Titan's south pole. Subsequent analysis of Cassini data revealed the cloud contained HCN ice, but the cloud's evolution has not been examined. We reviewed imagery of Titan's south pole between 2012 and the end of mission at Ls = 93°. We find evidence of cloud formation as early as Ls = 32° (April 2012), one terrestrial month earlier than previously reported, after which the cloud persists until Ls = 79° (mid 2016). The cloud top altitude descended from about 320 km at Ls = 32° to below 230 km by Ls = 79°, at which point it became obscured by atmospheric methane absorption. The cloud also grew laterally, remaining just beyond the terminator, suggesting the cloud marks a region of cold air in the polar stratosphere. These measurements place new constraints on Titan's polar stratospheric temperature structure and circulation during southern fall.